"... В кінці сценарію happy end”: наративна організація твору С. Курилова "Сам в океані" - Вещикова, Олена Сергіївна; Veshchykova, O. (My University, 2019)
Метою наукової розвідки є проаналізувати експлікацію авторського задуму у книзі “Сам в океані: історія втечі”. Специфіка наративної організації твору полягає в тому, що в ньому репрезентовано ніби дві авторські свідомості: Станіслава Курилова (автора, наратора) і його дружини Олени Генделєвої-Курилової (укладачки посмертного видання книги). О. ГенделєваКурилова компонувала текст з автентичних нотаток чоловіка, тому є авторкою композиції розділів як реалізації авторської інтенції зокрема і наративної стратегії загалом. У статті зроблено спробу з’ясувати авторську інтенцію в побудові наративної стратегії, розглянувши твір крізь захоплення головного героя духовними практиками, а також ураховуючи те, що прижиттєве видання книги Курилова мало назву “Шлях”. Відповідно, проведено паралелі між наративами С. Курилова і шляхом духовного розвитку йога, що включає в себе особистий шлях вісьмома щаблями раджа-йоги та соціальний шлях проходження дев’яти світів. Внутрішня фіксована фокалізація (за Ж. Женеттом), позиція всевідаючого наратора створюють передумови для численних флешбеків голосу оповідача. Це дає можливість реципієнтові простежити формування особистості головного героя і його шлях саморозвитку. З’ясовано, що композиція твору має нелійнійний характер: перший розділ “Втеча” є кульмінацією, “в кінці сценарію happy end” (фраза з пісні гурту “Антитіла”, кліп на яку знято за мотивами історії С. Курилова). Історія про втечу з лайнера є так званим “дзеркалом” – проміжним етапом між п’ятим і шостим світами, кризовим моментом у житті, коли людина усвідомлює свою істинну сутність і призначення на шляху. Подальші розділи “Пошук шляху”, “Море”, “Бог” презентують проходження оповідачем якогось із дев’яти світів. Наратор у розділі “Йога” оповідає про свій досвід в опануванні щаблів раджайоги. Включення О. Генделєвою-Куриловою деяких розділів до книги стає вмотивованим, якщо розглядати їхній зміст як проходження п’ятого світу — матеріальних і духовних цінностей людей. The scientific research aims to analyze the explication of the author’s intention in the book “Alone in the Ocean: a story of escape”. The specifics of the narrative organization of the work are that it seems to represent two authors’ consciousnesses: the consciousness of Stanislav Kurilov, who is the author and narrator and the one of his wife Olena Gendeleva-Kurilova, the compiler of the posthumous edition of the book. O. Gendeleva-Kurilova compiled the text from authentic notes of her husband; that is why she is the author of chapters’ composition as a realization of the very author’s intention in particular and narrative strategy in general. The article attempts to discover the author’s intention in development of the narrative strategy; the work is examined through the protagonist’s keenness on spiritual practices and taking into account the fact that the lifetime edition of Kurilov’s book was called “The Way”. Consequently, the parallels are drawn between Kurilov’s narratives and the way of the yoga’s spiritual growth that includes the personal journey via eight stages of raja yoga and the social way of passing the nine worlds. The internal fixed focalization (by G. Genette), the position of the all-knowing narrator create the preconditions for numerous flashbacks of the narrator’s voice. This enables the recipient to follow up the formation of the protagonist’s personality and his/her way of self-development. It is found that the composition of the work is non-linear: the first part “Escape” is the culmination, “at the end of the scenario will be the happy end” (a phrase from the song of the Ukrainian band “Antytila”, the clip of which was taken based on the story of S. Kurilov). The story of escaping from a liner is a so-called “mirror”, the intermediate stage between the fifth and sixth worlds, a crisis moment in life when one realizes his/her true essence and destinaiton on the way. Further parts “Finding the Way”, “Sea”, “God” represent the narrator’s passing one of the nine worlds. In the part called “Yoga” the narrator retells his experience in mastering of raja-yoga stages.The inclusion of certain parts by O. Gendeleva-Kurilova in the book becomes reasonable and motivated if we consider them as passing through the fifth world – the material and spiritual values of humans.
“… At the end of the scenario will be the happy end”: the narrative organization of S. Kurilov’s “Alone in the ocean”
Keywords: С. Курилов; наратив; гомодієгетичний наратор; пролепсис; йога; S. Kurilov; narrative; homodiegetic narrator; prolepsis; yoga